2008
DOI: 10.1371/journal.pmed.0050078
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Interleukin-6 Levels and Subsequent Risk of Coronary Heart Disease: Two New Prospective Studies and a Systematic Review

Abstract: BackgroundThe relevance to coronary heart disease (CHD) of cytokines that govern inflammatory cascades, such as interleukin-6 (IL-6), may be underestimated because such mediators are short acting and prone to fluctuations. We evaluated associations of long-term circulating IL-6 levels with CHD risk (defined as nonfatal myocardial infarction [MI] or fatal CHD) in two population-based cohorts, involving serial measurements to enable correction for within-person variability. We updated a systematic review to put … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
454
3
19

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 601 publications
(506 citation statements)
references
References 56 publications
30
454
3
19
Order By: Relevance
“…These results are consistent with recent meta-analyses of data from several prospective studies (including Caerphilly) for fibrinogen [6], plasma viscosity [7], leucocyte count [8] and CRP [9,10]. Interleukin-6 (IL-6) is a key pro-inflammatory cytokine which mediates expression of all these "downstream" inflammatory markers [11,12] (Fig. 2).…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…These results are consistent with recent meta-analyses of data from several prospective studies (including Caerphilly) for fibrinogen [6], plasma viscosity [7], leucocyte count [8] and CRP [9,10]. Interleukin-6 (IL-6) is a key pro-inflammatory cytokine which mediates expression of all these "downstream" inflammatory markers [11,12] (Fig. 2).…”
Section: Introductionsupporting
confidence: 88%
“…2). A recent systematic review of 17 prospective studies showed an overall odds ratio of 1.61 (95%CI 1.42,1.83) for subsequent risk of CHD for a two standard deviation increase in circulating levels of IL-6 [12]. Correction for within-person variability, corresponding to the longterm average IL-6 values increased the odds ratio to 3.34 (95%CI 2.45,4.56).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This estimate may derive from unique environmental factors or measurement error, but it may also result from gene-by-environment interactions that may inflate estimates of unique environmental effects. Unravelling the genetics of these pro-inflammatory parameters may greatly contribute to our understanding of the etiology of cardiac disease and major depression as chronic low-grade inflammation has repeatedly been shown to be associated with both (Cesari et al, 2003;Danesh et al, 2004Danesh et al, , 2008Humphries et al, 2007;Packard & Libby, 2008;Libby & Theroux, 2005;O'Brien et al, 2004;Woods et al, 2000;Penninx et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies on the possible pathways underlying the association between CVH and outcomes are scarce. Inflammatory and hemostatic blood biomarkers such as higher CRP (C‐reactive protein), IL‐6, and fibrinogen have been robustly associated with CHD or stroke and might represent relevant mediating factors to explore 13, 14, 15, 16. So far, only the Framingham study has explored the possible role of blood biomarkers in the associations between ideal CVH and outcomes 17.…”
Section: Introductionmentioning
confidence: 99%